Protective Effect of Cinnamon and Ginger on Acrylamide Induced Hepatotoxicity in Adult Male Albino Rats - El-sayed El-sayed Gawesh (Al-Azhar University, Faculty of Medicine (Damietta), 2021)
Background:Background: Acrylamide [ACR] is an essential chemical that is extensively used in many industries and also in laboratories such as treatment of drinking water, wastewater, and soil, production of paper, petroleum, mine, asphalt, dyes, adhesives, and polishes; it is known as a possible carcinogenic compound. Ginger oleoresin's hepatoprotective role can be attributed to its free radical scavenging, anti-inflammatory, and hypolipidemic activities and is partially mediated by the 6-gingerol, shogaol, and zingerone of its active component. Cinnamomum zeylanicum is used to treat many diseases and to prevent such diseases. Aim of the work:Evaluation of the effects of cinnamon and ginger extracts administration on Hepatotoxicity adult male albino rats. Materials and Methods: The groups were divided into five adult male albino rats of a local strain: Group I: acted as a control group with regular salines, group II: hepatotoxicity caused by acrylamid, groups III: hepatotoxicity plus cinnamon, group IV: hepatotoxicity plus ginger, group V: hepatotoxicity plus cinnamon and ginger. Samples for alanine aminotransferase [ALT], aspartate transfers of amino [AST], urea, creatinine, blood urea nitrogen (BUN), total cholesterol, triglyceride [TG], malondialdehyde, tumor necrosis factor α [TNF], superoxide dismutase [SOD], glutathione peroxidase [GPX], as well as total antioxidant [TAC] levels were obtained at the end of the experimental period.  Results: Administration of cinnamon and ginger to hepatotoxic rats led to a significant decrease in the mean value of ALT, AST, urea, creatinine, BUN, MDA, and TNF. In addition, it is associated with a significant increase of SOD, GPX, and TAC.  Conclusion: Cinnamon and ginger have a protective effect against abnormalities in hepatotoxic rats due to its several protective properties.